Genome size and GC content evolution of Festuca: ancestral expansion and subsequent reduction - Smarda, Petr; Bures, Petr; Horová, Lucie; Foggi, Bruno; Rossi, Graziano (Annals of botany, 2008)
BACKGROUND AND AIMS: Plant evolution is well known to be frequently associated with remarkable changes in genome size and composition; however, the knowledge of long-term evolutionary dynamics of these processes still remains very limited. Here a study is made of the fine dynamics of quantitative genome evolution in Festuca (fescue), the largest genus in Poaceae (grasses). METHODS: Using flow cytometry (PI, DAPI), measurements were made of DNA content (2C-value), monoploid genome size (Cx-value), average chromosome size (C/n-value) and cytosine + guanine (GC) content of 101 Festuca taxa and 14 of their close relatives. The results were compared with the existing phylogeny based on ITS and trnL-F sequences. KEY RESULTS: The divergence of the fescue lineage from related Poeae was predated by about a 2-fold monoploid genome and chromosome size enlargement, and apparent GC content enrichment. The backward reduction of these parameters, running parallel in both main evolutionary lineages of fine-leaved and broad-leaved fescues, appears to diverge among the existing species groups. The most dramatic reductions are associated with the most recently and rapidly evolving groups which, in combination with recent intraspecific genome size variability, indicate that the reduction process is probably ongoing and evolutionarily young. This dynamics may be a consequence of GC-rich retrotransposon proliferation and removal. Polyploids derived from parents with a large genome size and high GC content (mostly allopolyploids) had smaller Cx- and C/n-values and only slightly deviated from parental GC content, whereas polyploids derived from parents with small genome and low GC content (mostly autopolyploids) generally had a markedly increased GC content and slightly higher Cx- and C/n-values. CONCLUSIONS: The present study indicates the high potential of general quantitative characters of the genome for understanding the long-term processes of genome evolution, testing evolutionary hypotheses and their usefulness for large-scale genomic projects. Taken together, the results suggest that there is an evolutionary advantage for small genomes in Festuca.
Keywords: Phylogeny; retroelementy; molekulární evoluce; Polyploidy; polyploidie; fylogeneze; Festuca; Genome, Plant; genom rostlinný; Retroelements; Evolution, Molecular